2019
DOI: 10.1097/mpg.0000000000002207
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Diseases and School Absenteeism

Abstract: Objectives: Inflammatory bowel diseases (IBDs) are chronic diseases which negatively affect the schooling of children. The aim is to analyze school absenteeism and its causes in children followed for IBD. Methods: A prospective multicenter study of IBD patients aged from 5 to 18 years old, from September 2016 to June 2017. Data on absenteeism and its causes were collected via a monthly questionnaire completed by patients or their family by mail. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
3
12
0
4
Order By: Relevance
“…These findings are in line with other studies showing that children with IBD miss significantly more school than their healthy peers 25–27. Mackner et al 25 found that 20% of those with IBD missed >3 weeks of school (<92% attendance) compared with 4% of healthy adolescents, while Assa et al 26 found that the difference was greater, with 64% of those with IBD missing >3 weeks compared with 3% of healthy adolescents, although they had a relatively small sample of patients with IBD.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…These findings are in line with other studies showing that children with IBD miss significantly more school than their healthy peers 25–27. Mackner et al 25 found that 20% of those with IBD missed >3 weeks of school (<92% attendance) compared with 4% of healthy adolescents, while Assa et al 26 found that the difference was greater, with 64% of those with IBD missing >3 weeks compared with 3% of healthy adolescents, although they had a relatively small sample of patients with IBD.…”
Section: Discussionsupporting
confidence: 85%
“…However, these data are hypothetical and would require validation by moving hospital appointments to outside school hours in a cohort. Similarly, Eloi et al 27 found after excluding absences for scheduled care, the rate of school absenteeism of patients with IBD was significantly lower than the non-IBD group.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations